Microscopic experimental study on the heterogeneity and quantitative characterization of mineral grains and pore structures in coarse-grained glutenites - Shuai WANG; Ying XU; Yanbo ZHANG; Xulong YAO; Ling WANG (Meitan xuebao, 2024)
The heterogeneity of rock is the essential reason for its nonlinear macroscopic mechanical properties under external forces. To study the degree of influence of mineral particles and pore structure on the heterogeneity of rock, coarse-grained glutenites were subjected to CT scanning. The three-dimensional reconstruction technology and image threshold segmentation technology were used to reconstruct the mineral particles and pore structure. The characteristics of mineral particles and pore structures were quantified. The heterogeneity characteristics of coarse-grained glutenites were analyzed through statistical methods. A comprehensive index of rock heterogeneity was constructed to explore the key factors affecting rock heterogeneity. The results show that pore shape, pore diameter, and porosity can characterize the heterogeneity of the pore structure, where pore diameter is the key factor affecting the heterogeneity of the pore structure, porosity is a secondary factor, and pore shape is a non-critical factor; Mineral shape, mineral diameter, and the volume fraction of mineral particles can characterize the heterogeneity of mineral particles. The volume fraction of mineral particles is the key factor affecting the heterogeneity of mineral particles, mineral diameter is a secondary factor, and mineral shape is a non-critical factor. The comprehensive index of rock heterogeneity is consistent with the variation pattern of the mineral particle heterogeneity coefficient. The heterogeneity of rock is mainly determined by the heterogeneity of mineral particles, with the volume fraction of mineral particles being the core factor affecting rock heterogeneity, and mineral shape being the least influential factor. Quantifying the heterogeneity of mineral particles and pore structure inside the rock can more accurately assess the overall performance and stability of the rock. It can be used to predict potential risks in rock engineering and adopt corresponding preventive measures to ensure the safety and stability of the projects.